Phase change material with a phase change temperature of 2 to 8°C and preparation method thereof
By using low-temperature phase change materials composed of a variety of additives in the medical cold chain transportation range of 2 to 8°C, the problems of low density, low latent heat and poor cycle stability in the prior art are solved, and longer insulation time and better cycle stability are achieved.
Patent Information
- Application Number
- CN202211145914.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-09-20
AI Technical Summary
In the prior art, the phase change materials required for medical cold chain transportation within the range of 2 to 8°C have problems such as small density, low latent heat per unit volume, low thermal conductivity, high volume expansion rate and easy leakage, resulting in short insulation time and poor circulation stability.
A low-temperature phase change material consisting of phase change refrigerant, nucleating agent, thickening agent, crystal form improvement agent, performance optimizer and water is used to improve the phase change temperature, latent heat and thermal conductivity, while reducing the expansion rate and supercooling degree.
The phase transition temperature is between 2 and 8°C, the latent heat of phase transition is >260kJ/kg, the thermal conductivity is >1.1W/(m.K), the density is >1.6g/cm3, the volume expansion rate is <0.5% and the supercooling degree is <1°C, and the circulation stability of the material is significantly improved.
Smart Images

Figure BDA0003855476720000251 
Figure BDA0003855476720000261
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change materials, and in particular to a phase change material with a phase change temperature of 2-8°C and a preparation method thereof. Background Art
[0002] With the rapid development of modern logistics and the increasing demand for cold chain medicines, pharmaceutical cold chain logistics has also received more attention. In particular, during the cold chain transportation of medicines in the range of 2 to 8°C, strict control of temperature and fluctuation range is required to store or transport medicines, vaccines, blood products and other items to ensure their quality and effectiveness. However, the demand for medical cold chain transportation in the range of 2 to 8°C is huge and the cost is too high. Therefore, reducing the cost of medical cold chain transportation in the range of 2 to 8°C has great economic benefits.
[0003] At present, inorganic hydrated salts and organic phase change materials are often used in pharmaceutical cold chain transportation phase change materials. However, inorganic hydrated salts have disadvantages such as phase separation and easy leakage, while organic phase change materials also have disadvantages such as low latent heat and flammability. In the prior art, alcohol phase change material matrices are also used, but they have the characteristics of low density, low latent heat of phase change per unit volume, low thermal conductivity, high volume expansion rate and easy leakage; low density and light weight of phase change material per unit volume lead to low latent heat of phase change per unit volume, so in actual application, the insulation time is short under the same conditions; high volume expansion rate will cause the ice block (or other fixed container) to be filled with less phase change material under the same volume, reducing the insulation time; and the higher the volume expansion rate, the easier it is to cause the ice block (or other container) to bulge, expand, or even rupture, and it is easy to leak. Summary of the invention
[0004] The technical problem to be solved by the present invention is that, in view of the defects of the prior art, a phase change material with a phase change temperature of 2 to 8°C and a preparation method thereof are provided. The phase change material has good stability, low material cost, simple preparation process, high density, low expansion rate, high phase change latent heat, high thermal conductivity, good effect after multiple cycles, and long cycle life.
[0005] The technical solution adopted by the present invention to solve the technical problem is: a low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by weight: 30 to 50 parts of a phase change refrigerant, 0.3 to 3 parts of a nucleating agent, 0.5 to 8 parts of a thickener, 0.1 to 1 parts of a crystal modifier, 1 to 5 parts of a performance optimizer, and 35 to 70 parts of water;
[0006] The phase-change coolant comprises at least two of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, barium hydroxide, calcium hydroxide, ammonia water, potassium bicarbonate, sodium bicarbonate, potassium chloride, sodium chloride, barium chloride, potassium nitrate, sodium acetate, sodium sulfate, and disodium hydrogen phosphate;
[0007] The crystal modifier is at least one of diatomaceous earth, activated clay, soluble starch, fumed silica, viscose fiber, acetate fiber, polyester, acrylic fiber, spandex, chloroprene, glass fiber, and asbestos;
[0008] The performance optimizer is a spherical structure, and the outer surface of the performance optimizer is coated with a positive ion layer.
[0009] Furthermore, in the phase-change refrigerant, the particle size of the crystal modifier is preferably 20 to 100 μm.
[0010] Furthermore, in the phase-change refrigerant, the nucleating agent is preferably at least one of nano-carbon powder, graphite powder, nano-zinc oxide, nano-aluminum oxide, nano-copper, nano-silicon nitride, carbon nanotubes, and carboxylated multi-walled carbon nanotubes.
[0011] Furthermore, in the phase-change refrigerant, the particle size of the nucleating agent is preferably 10 to 200 μm.
[0012] Furthermore, in the phase change cool storage agent, the thickener is preferably at least one of polyacrylamide, sodium polyacrylate, sodium carboxymethyl cellulose, sodium hydroxymethyl cellulose, xanthan gum, guar gum, activated clay, gelatin, attapulgite, gum arabic, pectin, agar, tamarind gum, β-cyclodextrin, sodium carboxymethyl starch, and hydroxypropyl starch.
[0013] Furthermore, in the phase-change refrigerant, the particle size of the thickener is preferably 20 to 100 μm. Furthermore, in the phase-change refrigerant, the performance optimizer is preferably at least one of gold sol, silver sol, copper sol, and aluminum sol.
[0014] Furthermore, in the phase-change refrigerant, the particle size of the performance optimizer is preferably 1 nm to 100 nm.
[0015] Furthermore, in the phase change refrigerant, the positive ion layer is preferably H + layer.
[0016] A method for preparing the above-mentioned low-temperature phase change material with a phase change temperature of 2 to 8° C. comprises the following steps:
[0017] S1, taking a phase change refrigerant in proportion, slowly adding it into water to dissolve, stirring and mixing evenly to obtain a first mixed solution;
[0018] S2, adding a nucleating agent to the first mixed solution, stirring and mixing, and stopping stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state, to obtain a second mixed solution;
[0019] S3, adding a crystal form modifier to the second mixed solution, stirring and mixing, and stopping stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state, to obtain a third mixed solution;
[0020] S4, adding the performance optimizer to the third mixed solution, stirring and mixing, and stopping stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state, to obtain a fourth mixed solution;
[0021] S5. Add a thickener to the fourth mixed solution, stir and mix evenly, and stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state to obtain a phase change material.
[0022] Furthermore, in the preparation method of the phase-change refrigerant, preferably in step S1, the stirring temperature is 25 to 35° C., the stirring rate is 400 to 600 rpm, and the stirring time is 1 to 2 h.
[0023] Furthermore, in the preparation method of the phase change refrigerant, preferably in step S2, the stirring temperature is 25 to 35° C., the stirring rate is 400 to 600 rpm, and the stirring time is 1 to 2 h.
[0024] Furthermore, in the preparation method of the phase change refrigerant, preferably in step S3, the stirring temperature is 25 to 35° C., the stirring rate is 400 to 600 rpm, and the stirring time is 1 to 2 h.
[0025] Furthermore, in the preparation method of the phase-change refrigerant, preferably in step S4, the stirring temperature is 25 to 35° C., the stirring rate is 400 to 600 rpm, and the stirring time is 1 to 2 h.
[0026] Furthermore, in the preparation method of the phase-change refrigerant, preferably in step S5, the stirring temperature is 25-35° C., the stirring rate is 600-800 rpm, and the stirring time is 2-4 h.
[0027] Beneficial effects of the present invention: The present invention provides a low-temperature phase change material with a phase change temperature of 2 to 8°C and a preparation method thereof. The phase change material of the present invention comprises a phase change refrigerant, a nucleating agent, a thickener, a crystal modifier, a performance optimizer, and water. A variety of inorganic salts selected from potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, barium hydroxide, calcium hydroxide, ammonia water, potassium bicarbonate, sodium bicarbonate, potassium chloride, sodium chloride, barium chloride, potassium nitrate, sodium acetate, sodium sulfate, and disodium hydrogen phosphate are used as phase change refrigerants, which make up for the problems of too small or too large phase change temperature, reduced phase change latent heat, and low cycle stability when a single phase change refrigerant is used. In addition, adding a crystal modifier to the system can well control the crystal particle size, prevent the crystal from growing excessively, make the low eutectic mixture crystals small and uniform, and can also increase the phase change temperature of the phase change refrigerant, so that the phase change temperature is increased from 3°C to about 5°C. More importantly, the crystal modifier selected by the present invention The modifier has a large specific surface energy, good small crystal adsorption, and can promote crystal growth. It has an excellent adsorption effect on the characteristics of the fine grains of the phase change refrigerant selected by the present invention, and forms a network structure after adsorption, which enhances the binding force between the ions of the phase change material. When a solid-liquid phase change occurs, more energy is required to destroy this network structure, thereby significantly increasing the latent heat of the phase change and greatly enhancing the cycle stability; the performance optimizer with a spherical structure added to the system can be connected with the network structure formed by the crystal modifier and the phase change refrigerant to form a three-dimensional layered super-large network structure, which can significantly improve the binding force of the network structure; in the process of solid-liquid phase change, a very large energy is required to destroy the three-dimensional layered structure, which can significantly improve the cycle stability performance of the material system, reduce the rate of change of the phase change temperature before and after the cycle, and keep the phase change temperature stable; the latent heat of the phase change material can be significantly increased. Adding a nucleating agent into the system can play a nucleating role, which can greatly reduce the supercooling degree, and at the same time can significantly improve the thermal conductivity of the material system, thereby increasing the heat exchange rate, controlling the temperature more quickly, and obtaining a phase change material with high thermal conductivity and low supercooling degree; adding a thickener into the system can play a thickening role, prevent phase stratification, and improve the cyclic stability performance; the phase change material of the present invention has high thermal conductivity, high density, low expansion rate, high phase change latent heat, good stability, low material cost, safety and non-toxicity, and a simple preparation process. The phase change temperature of the phase change material of the present invention is 2-8°C, the phase change latent heat is >260kJ / kg, the thermal conductivity is >1.1W / (mK), the density is >1.6g / cm3, the volume expansion rate is <0.5%, and the supercooling degree is <1°C. After 200 cycles, it still has a good phase change latent heat. DETAILED DESCRIPTION
[0028] A low-temperature phase change material with a phase change temperature of 2 to 8°C comprises the following components in parts by mass: 30 to 50 parts of a phase change coolant, 0.3 to 3 parts of a nucleating agent, 0.5 to 8 parts of a thickener, 0.1 to 1 parts of a crystal modifier, 1 to 5 parts of a performance modifier, and 35 to 70 parts of water; the phase change coolant comprises at least two of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, barium hydroxide, calcium hydroxide, ammonia water, potassium bicarbonate, sodium bicarbonate, potassium chloride, sodium chloride, barium chloride, potassium nitrate, sodium acetate, sodium sulfate, and disodium hydrogen phosphate; the crystal modifier is at least one of diatomaceous earth, activated clay, soluble starch, fumed silica, viscose fiber, acetate fiber, polyester, acrylic fiber, spandex, chloroprene, glass fiber, and asbestos; the performance optimizer is a spherical structure, and the outer surface of the performance optimizer is coated with a positive ion layer.
[0029] The present invention provides a low-temperature phase change material with a phase change temperature of 2 to 8°C and a preparation method thereof. The phase change material of the present invention comprises a phase change refrigerant, a nucleating agent, a thickener, a crystal modifier, and water. A variety of inorganic salts selected from potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, barium hydroxide, calcium hydroxide, ammonia water, potassium bicarbonate, sodium bicarbonate, potassium chloride, sodium chloride, barium chloride, potassium nitrate, sodium acetate, sodium sulfate, and disodium hydrogen phosphate are used as phase change refrigerants, thereby compensating for the problems of too small or too large phase change temperature, reduced phase change latent heat, and reduced cycle stability caused by using a single phase change refrigerant. In addition, adding a crystal modifier to the system can well control the crystal particle size, prevent the crystal from growing excessively, make the low eutectic mixture crystals small and uniform, and can also increase the phase change temperature of the phase change refrigerant, so that the phase change temperature is increased from 3°C to about 5°C. More importantly, the crystal modifier selected by the present invention has a large specific surface energy and good small crystal adsorption. It can promote crystal growth and has an excellent adsorption effect on the characteristics of the fine grains of the phase change refrigerant selected by the present invention. After adsorption, a network structure is formed to enhance the binding force between the ions of the phase change material. When a solid-liquid phase change occurs, more energy is required to destroy the network structure, thereby significantly increasing the latent heat of phase change and greatly enhancing the cycle stability. The performance optimizer includes a basic atomic nucleus and a negative ion layer coated on the basic atomic nucleus. The performance optimizer with a spherical structure added to the system can be connected with the network structure formed by the crystal modifier and the phase change refrigerant to form a three-dimensional layered super-large network structure, which can significantly improve the binding force of the network structure. In the process of solid-liquid phase change, a very large energy is required to destroy the three-dimensional layered structure, which can greatly improve the cycle stability of the material system, reduce the rate of change of the phase change temperature before and after the cycle, and keep the phase change temperature stable. The latent heat of phase change of the phase change material can be significantly increased. Adding a nucleating agent into the system can play a nucleating role, which can greatly reduce the supercooling degree, and at the same time can significantly improve the thermal conductivity of the material system, thereby increasing the heat exchange rate, controlling the temperature more quickly, and obtaining a phase change material with high thermal conductivity and low supercooling degree; adding a thickener into the system can play a thickening role, prevent phase stratification, and improve the cyclic stability performance; the phase change material of the present invention has high density, low expansion rate, high phase change latent heat, good stability, low material cost, safety and non-toxicity, and a simple preparation process. The phase change temperature of the phase change material of the present invention is 2-8°C, the phase change latent heat is >260kJ / kg, the thermal conductivity is >1.1W / (mK), the density is >1.6g / cm3, the volume expansion rate is <0.5%, and the low supercooling degree is <1°C. After 200 cycles, it still has a good phase change latent heat.
[0030] Furthermore, the particle size of the crystal modifier is preferably 20 to 100 μm. The particle size is controlled mainly to control the dispersion effect of the crystal modifier in the solution system and better control the crystal particle size. Too large crystals are not conducive to dispersion and dissolution in the solution, and too small crystals reduce the effect of controlling the crystal particle size. Therefore, the particle size is controlled mainly to better play the role of the crystal modifier.
[0031] Furthermore, the preferred nucleating agent is at least one of nano-carbon powder, graphite powder, nano-zinc oxide, nano-aluminum oxide, nano-copper, nano-silicon nitride, carbon nanotubes, and carboxylated multi-walled carbon nanotubes. By the non-uniform nucleation mechanism, adding a nucleating agent to the phase change system of the present invention can effectively reduce the supercooling of the phase change material, and this requires that the nucleating agent and the phase change refrigerant match each other in terms of crystal structure characteristics, lattice parameter size, physical properties, etc., and that a thickener and a crystal modifier are added in combination, so that the particle size of the nucleating agent is controlled to be 10μm to 200μm. The nucleating agent is used to play the role of a crystal nucleus in the solidification process of the phase change material, promote crystal growth, and reduce the barrier to nucleation growth; the particle size within this range can play the role of a crystal nucleus in the solidification process and promote crystal growth , reducing the barrier to nucleation growth, and can also effectively reduce the supercooling of the phase change material; if the particle size is too small, it is not easy to act as a crystal nucleus for nucleation growth, and it cannot significantly reduce the driving force for crystallization, and the effect of reducing supercooling is not good; if the particle size is too large, the crystals cannot grow on the surface of large grains during the crystallization process, so they cannot play a role as crystal nuclei, and cannot completely reduce the driving force for crystallization, and cannot play a role in reducing supercooling; and the nucleating agent used above is a high thermal conductivity material. High thermal conductivity materials as nucleating agents can increase the thermal conductivity of the phase change material system, thereby increasing the heat exchange rate and controlling the temperature more quickly.
[0032] Further, the preferred thickener is polyacrylamide, sodium polyacrylate, sodium carboxymethyl cellulose, sodium hydroxymethyl cellulose, xanthan gum, guar gum, activated clay, gelatin, attapulgite, gum arabic, pectin, agar, tamarind gum, β-cyclodextrin, sodium carboxymethyl starch, and at least one of hydroxypropyl starch; the thickener added to the system of the present invention can play a thickening role, so that the solid particles or crystal nuclei of the phase change refrigerant in the system can be evenly distributed in the solution without being affected by gravity and stratification, effectively improving the phase separation problem of the phase change material, preventing phase stratification, and improving the cycle stability. The thickener forms a network or chain structure through the connection with the raw material molecules, especially the connection with the water molecules, thereby increasing the viscosity of the system; if the thickener particle size is too large or too small, it is not conducive to the phase change material to form a network or chain structure, and the thickening effect is reduced, so the particle size of the thickener is controlled to be 20 to 100 μm.
[0033] Furthermore, the performance optimizer is preferably at least one of gold sol, silver sol, copper sol, and aluminum sol. The performance optimizer (gold sol, silver sol, copper sol, and aluminum sol) itself includes a basic atomic nucleus (atom gold, or atom silver, or atom aluminum, or atom copper) and a negative ion layer surrounding it. It is further preferred that the outermost layer of the performance optimizer is coated with a positive ion layer, such as hydrogen ions, or Na + , K + , Ca2 + , Ba 2+ etc., except H + The positive ions outside the phase change refrigerant are preferably the same or of the same family as the ions contained in the phase change refrigerant. The negative ion layer and the positive ion layer will not react. Positive and negative ions attract each other, but the two are in a dynamic equilibrium process. + The performance optimizer can be pickled with an acid solution such as hydrochloric acid or sulfuric acid to make the negative ion outer layer of the performance optimizer coated with H + Ion layer, H + It is dispersed in the solution in the form of spherical small particles. In a specific embodiment, 100 ml of 1% gold sol aqueous solution is heated to boiling, and 0.7-1 ml of 1% trisodium citrate (Na3C6H5O7·2H2O) aqueous solution is added under constant temperature heating and stirring, and vacuum heating is maintained at 100°C for 30 minutes. After cooling, the solution is adjusted to 1% with distilled water, and the negative ion outer layer of the gold sol is coated with an H+ ion layer, and H+ is dispersed in the solution. First, the crystal modifier can adsorb the phase change refrigerant to form a network structure. The phase change refrigerant is mainly alkaline and can form a strong adsorption bonding force with the performance optimizer with an H+ layer. Then, because the performance optimizer is a spherical particle, the previously formed network structure can be formed into a larger three-dimensional layered structure in the horizontal and vertical directions, which can significantly improve the bonding force of the network structure; in the process of solid-liquid phase change, a very large amount of energy is required to destroy the three-dimensional layered structure, which can greatly improve the cyclic stability of the material system, reduce the rate of change of the phase change temperature before and after the cycle, keep the phase change temperature stable, and significantly increase the phase change latent heat of the phase change material. If the particle size of the performance optimizer is too large or too small, it is not conducive to the formation of a three-dimensional layered ultra-large network structure, which affects the stability of the phase change material, so the particle size of the performance optimizer is controlled to be 1nm~100nm.
[0034] The nucleating agent used in the present invention is mainly carbon powder, graphite powder, nano-alumina and other materials with high thermal conductivity, so it can significantly improve the thermal conductivity of the phase change material.
[0035] The phase change refrigerant material of the present invention adopts an inorganic material which has the property of high density itself, and the proportion of the inorganic material in the whole phase change material system is also very high, which can improve the density of the phase change material system of the present invention, which is about twice the density of the organic phase change material. The high density of the phase change material per unit volume makes the phase change enthalpy per unit volume high, and the phase change latent heat per unit volume is about 430 J / ml. Therefore, in actual application, the insulation time is long under the same conditions, and the unit mass latent heat of the phase change material of the present invention is about 260 kJ / kg; secondly, the phase change refrigerant selected by the present invention is an inorganic salt material, and the connection between the ions in its aqueous solution mainly exists in the form of ionic bonds. When the solid-liquid phase change occurs, more energy is required to destroy the ionic bonds, so the phase change latent heat is high; furthermore, the crystal form modifier added in the present invention has a good adsorption effect on the fine grains of the phase change refrigerant selected by the present invention, and forms a network structure, so that the binding force between the ions is stronger, and when the solid-liquid phase change occurs, more energy is required to destroy the network structure; in summary, the phase change material of the present invention has a high phase change latent heat.
[0036] The type and ratio of the phase change refrigerant selected in the present invention have excellent cycle stability; secondly, the selected nucleating agent, thickener, and crystal modifier have a reinforcing effect on the performance of the entire material system; furthermore, the crystal modifier added in the present invention has an adsorption effect on the fine grains of the phase change refrigerant selected in the present invention, and forms a network structure, which can significantly improve the cycle stability of the phase change material. In summary, the phase change material of the present invention has good cycle stability.
[0037] A method for preparing the above-mentioned low-temperature phase change material with a phase change temperature of 2 to 8° C. comprises the following steps:
[0038] S1. Take a phase-change refrigerant in proportion, slowly add it into water to dissolve, stir and mix evenly to obtain a first mixed solution.
[0039] Furthermore, preferably, in step S1, the stirring temperature is 25-35°C, the stirring rate is 400-600rpm, and the stirring time is 1-2h. The temperature and stirring rate are controlled mainly to accelerate the dissolution of the phase-change refrigerant and stir evenly. The temperature is generally not too low and is generally kept above room temperature; at the same time, the temperature is not too high to prevent water from volatilizing during the stirring process. The stirring time is controlled to fully dissolve the phase-change refrigerant and form a uniform first mixed solution.
[0040] S2. Add a nucleating agent to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state to obtain a second mixed solution.
[0041] Further, preferably in step S2, the stirring temperature is 25-35°C, the stirring rate is 400-600rpm, and the stirring time is 1-2h. The temperature and stirring rate are controlled mainly to accelerate the dissolution of the nucleating agent and stir evenly. The temperature is generally not too low or too high, and is generally maintained at 25-35°C to prevent the volatilization of water during the stirring process due to the high temperature. At the same time, the nucleating agent can also well reduce the supercooling of the phase change material system, promote crystal growth, and reduce the barrier of nucleation growth; the stirring time is controlled to fully dissolve the nucleating agent to form a uniform second mixed solution.
[0042] S3, adding a crystal form modifier to the second mixed solution, stirring and mixing, and stopping stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state to obtain a third mixed solution.
[0043] Further, preferably in step S3, the stirring temperature is 20-35°C, the stirring rate is 400-600rpm, and the stirring time is 1-2h. The temperature and stirring rate are controlled mainly to accelerate the dissolution of the crystal modifier and stir evenly. The temperature is generally not too low or too high, and is generally maintained at 20-35°C to prevent the volatilization of water during the stirring process due to the high temperature. At the same time, the crystal modifier has an excellent adsorption effect on the characteristics of the fine grains of the phase change refrigerant selected by the present invention, and forms a network structure after adsorption, which enhances the binding force between the ions of the phase change material. When the solid-liquid phase change occurs, more energy is required to destroy this network structure, thereby significantly increasing the latent heat of phase change and greatly enhancing the cycle stability; the stirring time is controlled to fully dissolve the crystal modifier to form a uniform third mixed solution.
[0044] S4. Add the performance optimizer to the third mixed solution, stir and mix, and stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state to obtain a fourth mixed solution.
[0045] Further, preferably in step S4, the stirring temperature is 25-35°C, the stirring rate is 400-600rpm, and the stirring time is 1-2h. The temperature and stirring rate are controlled mainly to accelerate the dispersion of the performance optimizer and stir evenly. The temperature is generally not too low and is generally kept above room temperature; at the same time, the temperature cannot be too high to prevent water from volatilizing during the stirring process. The stirring time is to allow the performance optimizer to fully dissolve and form a uniform fourth mixed solution. Adding a performance optimizer to the system can connect the network structure formed by the crystal form modifier and the phase change material to form a three-dimensional layered super-large network structure, which can significantly improve the binding force of the network structure; in the process of solid-liquid phase change, a very large energy is required to destroy the three-dimensional layered structure, which can greatly improve the cyclic stability of the material system, reduce the rate of change of the phase change temperature before and after the cycle, keep the phase change temperature stable, and significantly increase the phase change latent heat of the phase change material.
[0046] S5. Add a thickener to the fourth mixed solution, stir and mix evenly, and stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state to obtain a phase change material.
[0047] Furthermore, preferably in step S5, the stirring temperature is 20-35°C, the stirring rate is 600-800rpm, and the stirring time is 2-4h. The temperature, stirring rate and time are controlled mainly to accelerate the dissolution of the thickener and stir evenly. The temperature is generally not too low or too high, and is generally maintained at 20-35°C to prevent the water from volatilizing during the stirring process due to the high temperature, and at the same time make it fully dissolved, enhance the viscosity of the phase change system, so that the solid particles or crystal nuclei of the phase change refrigerant in the solution can be evenly distributed in the system solution without being affected by gravity and stratification, effectively improving the phase separation problem of the phase change material.
[0048] The following is a detailed description through specific implementation methods:
[0049] Example 1
[0050] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 45 parts of a phase change refrigerant (35 parts of sodium hydroxide and 10 parts of sodium carbonate), 1.5 parts of a nucleating agent (1 part of nano zinc oxide and 0.5 parts of carbon nanotubes, with a controlled particle size of about 10 μm), 4 parts of a thickener xanthan gum (with a controlled particle size of about 20 μm), 0.1 parts of a crystal modifier diatomaceous earth (with a controlled particle size of about 20 μm), 5 parts of a performance optimizer gold sol (with the outer surface of each part coated with a positive ion layer, the positive ions being H +, controlling the particle size to be about 1nm), 44.4 parts of water. Among them, sodium hydroxide and sodium carbonate can be replaced by at least two of potassium carbonate, potassium hydroxide, barium hydroxide, calcium hydroxide, ammonia water, potassium bicarbonate, sodium bicarbonate, potassium chloride, sodium chloride, barium chloride, potassium nitrate, sodium acetate, sodium sulfate, and disodium hydrogen phosphate, as long as the total amount of phase change refrigerant meets 45 parts; nano zinc oxide and carbon nanotubes can be replaced by at least one of nano carbon powder, graphite powder, nano alumina, nano copper, nano silicon nitride, and carboxylated multi-walled carbon nanotubes, as long as the total amount of nucleating agent meets 1.5 parts; xanthan gum can be replaced by polyacrylamide, sodium polyacrylate, sodium carboxymethyl cellulose, hydroxymethyl At least one of sodium cellulose, guar gum, activated clay, gelatin, attapulgite, gum arabic, pectin, agar, tamarind gum, β-cyclodextrin, sodium carboxymethyl starch, and hydroxypropyl starch, as long as the total amount of the thickener is 4 parts; diatomaceous earth can be replaced by at least one of activated white clay, soluble starch, fumed silica, viscose fiber, acetate fiber, polyester, acrylic fiber, spandex, chloroprene, glass fiber, and asbestos, as long as the total amount of the crystal modifier is 0.1 parts; gold sol can be replaced by at least one of silver sol, copper sol, and aluminum sol, as long as the total amount of gold sol is 5 parts.
[0051] The preparation method comprises the following steps:
[0052] S1. Take 35 parts of sodium hydroxide and 10 parts of sodium carbonate as phase change refrigerant in proportion, slowly add them into 44.4 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0053] S2. Add 1 part of nucleating agent nano zinc oxide and 0.5 parts of carbon nanotubes to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 20° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0054] S3. Add 0.1 parts of diatomaceous earth as a crystal form modifier to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 h to obtain a third mixed solution.
[0055] S4. Add 5 parts of performance optimizer gold sol to the third mixed solution, stir and mix, stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a fourth mixed solution.
[0056] S5. Add 4 parts of thickener xanthan gum to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 20° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0057] Example 2
[0058] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 50 parts of a phase change refrigerant (including 30 parts of potassium hydroxide and 20 parts of potassium carbonate), 3 parts of a nucleating agent graphite powder (controlling the particle size to be about 105 μm), 8 parts of a thickener polyacrylamide (controlling the particle size to be about 60 μm), 1 part of a crystal modifier activated clay (controlling the particle size to be about 60 μm), 3 parts of a performance optimizer gold sol (the outer surface of each of which is coated with a positive ion layer, the positive ion is K + , controlling the particle size to be about 45nm), 35 parts of water.
[0059] The preparation method comprises the following steps:
[0060] S1. Take 30 parts of potassium hydroxide and 20 parts of potassium carbonate as phase change refrigerant in proportion, slowly add them into 35 parts of water to dissolve, stir and mix evenly, the stirring temperature is 27° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0061] S2. Add 3 parts of nucleating agent graphite powder to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 27° C., the stirring rate is 500 rpm, and the stirring time is 1.5 h to obtain a second mixed solution.
[0062] S3. Add 1 part of activated clay as a crystal modifier to the second mixed solution, stir and mix, and stop stirring when the crystal modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 27° C., the stirring rate is 500 rpm, and the stirring time is 1.5 h to obtain a third mixed solution.
[0063] S4. Add 3 parts of performance optimizer gold sol to the third mixed solution, stir and mix, stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 27° C., the stirring rate is 500 rpm, and the stirring time is 1.5 h to obtain a fourth mixed solution.
[0064] S5. Add 8 parts of thickener polyacrylamide to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 27° C., the stirring rate is 700 rpm, and the stirring time is 3 h to obtain a phase change material.
[0065] Example 3
[0066] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 30 parts of a phase change refrigerant (including 20 parts of barium hydroxide and 10 parts of barium chloride), 0.3 parts of a nucleating agent nano-carbon powder (the particle size is controlled to be about 200 μm), 1 part of a thickener sodium carboxymethyl cellulose (the particle size is controlled to be about 100 μm), 0.1 parts of a crystal modifier soluble starch (the particle size is controlled to be about 100 μm), 1 part of a performance optimizer silver sol (the outer surface is coated with a positive ion layer, and the positive ion is Ba 2+ , controlling the particle size to be about 100 nm), 67.6 parts of water.
[0067] The preparation method comprises the following steps:
[0068] S1. Take 20 parts of barium hydroxide and 10 parts of barium chloride as phase change refrigerant in proportion, slowly add them into 67.6 parts of water to dissolve, stir and mix evenly, the stirring temperature is 35° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a first mixed solution.
[0069] S2. Add 0.3 parts of nucleating agent nano-carbon powder to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 35° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a second mixed solution.
[0070] S3. Add 0.1 parts of soluble starch as a crystal form modifier to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 35° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a third mixed solution.
[0071] S4. Add 1 part of performance optimizer silver sol to the third mixed solution, stir and mix, stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 35° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a fourth mixed solution.
[0072] S5. Add 1 part of sodium carboxymethyl cellulose as a thickener to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 35° C., the stirring rate is 800 rpm, and the stirring time is 4 hours to obtain a phase change material.
[0073] Example 4
[0074] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 50 parts of a phase change refrigerant (including 30 parts of potassium carbonate and 20 parts of sodium sulfate), 3 parts of a nucleating agent, nano zinc oxide (controlling a particle size of about 180 μm), 0.5 parts of a thickener, β-cyclodextrin (controlling a particle size of about 70 μm), 0.5 parts of a crystal modifier, fumed silica (controlling a particle size of about 80 μm), 3 parts of a performance optimizer, copper sol (the outer surface of each of which is coated with a positive ion layer, the positive ion is H + , controlling the particle size to be about 30nm), 43 parts of water.
[0075] The preparation method comprises the following steps:
[0076] S1. Take 30 parts of potassium carbonate and 20 parts of sodium sulfate as phase change refrigerant in proportion, slowly add them into 43 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0077] S2. Add 3 parts of nano zinc oxide as a nucleating agent to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0078] S3. Add 0.5 parts of crystal form modifier fumed silica to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a third mixed solution.
[0079] S4. Add 3 parts of copper sol, a performance optimizer, to the third mixed solution, stir and mix, and stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 35° C., the stirring rate is 550 rpm, and the stirring time is 1.2 h to obtain a fourth mixed solution.
[0080] S5. Add 0.5 parts of thickener β-cyclodextrin to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0081] Example 5
[0082] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 35 parts of a phase change refrigerant (including 20 parts of sodium bicarbonate and 15 parts of sodium chloride), 2 parts of a nucleating agent, nano copper powder (controlling a particle size of about 120 μm), 7 parts of a thickener, gelatin, and 1 part of sodium carboxymethyl starch (controlling a particle size of about 70 μm), 0.7 parts of a crystal modifier, viscose fiber (controlling a particle size of about 80 μm), and 3 parts of a performance optimizer, aluminum sol (the outer surface of each of which is coated with a positive ion layer, the positive ion is Na + , controlling the particle size to be about 25nm), 51.3 parts of water.
[0083] The preparation method comprises the following steps:
[0084] S1. Take 20 parts of sodium bicarbonate and 15 parts of sodium chloride as phase change refrigerant in proportion, slowly add them into 51.3 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0085] S2. Add 2 parts of nucleating agent nano copper powder to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0086] S3. Add 0.7 parts of crystal modifier viscose fiber to the second mixed solution, stir and mix, and stop stirring when the crystal modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a third mixed solution.
[0087] S4. Add 3 parts of performance optimizer aluminum sol to the third mixed solution, stir and mix, and stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 35° C., the stirring rate is 550 rpm, and the stirring time is 1.2 h to obtain a fourth mixed solution.
[0088] S5. Add 7 parts of thickener gelatin and 1 part of sodium carboxymethyl starch to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25°C, the stirring rate is 600 rpm, and the stirring time is 2 hours to obtain a phase change material.
[0089] Example 6
[0090] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 40 parts of a phase change refrigerant (including 25 parts of sodium hydroxide, 10 parts of calcium hydroxide, and 5 parts of sodium acetate), 0.8 parts of a nucleating agent carboxylated multi-walled carbon nanotubes (controlling a particle size of about 120 μm), 2 parts of a thickener activated clay and 6 parts of agar (controlling a particle size of about 70 μm), 0.7 parts of a crystal modifier spandex (controlling a particle size of about 80 μm), 2 parts of a performance optimizer copper sol (the outer surface of each of the copper sols is coated with a positive ion layer, and the positive ions are H + , controlling the particle size to be about 15nm), 48.5 parts of water.
[0091] The preparation method comprises the following steps:
[0092] S1. Take 25 parts of phase change refrigerant sodium hydroxide, 10 parts of calcium hydroxide, and 5 parts of sodium acetate in proportion, slowly add them into 48.5 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0093] S2. Add 0.8 parts of carboxylated multi-walled carbon nanotubes as a nucleating agent to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0094] S3. Add 0.7 parts of the crystal modifier spandex to the second mixed solution, stir and mix, and stop stirring when the crystal modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a third mixed solution.
[0095] S4. Add 2 parts of the performance optimizer copper sol to the third mixed solution, stir and mix, and stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 35° C., the stirring rate is 550 rpm, and the stirring time is 1.2 h to obtain a fourth mixed solution.
[0096] S5. Add 2 parts of thickener activated clay and 6 parts of agar to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0097] Comparative Example 1
[0098] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 70 parts of a phase change refrigerant (including 60 parts of sodium carbonate decahydrate and 10 parts of potassium chloride), 3 parts of a nucleating agent, nano zinc oxide (controlling a particle size of about 100 μm), 1 part of a thickener, sodium carboxymethyl cellulose (controlling a particle size of about 70 μm), 0.1 part of a crystal modifier, diatomaceous earth (controlling a particle size of about 20 μm), 2 parts of a performance optimizer, gold sol (the outer surface of each of which is coated with a positive ion layer, the positive ion is H + , controlling the particle size to be about 1 nm), 23.9 parts of water.
[0099] The preparation method comprises the following steps:
[0100] S1. Take 60 parts of sodium carbonate decahydrate and 10 parts of potassium chloride as phase change refrigerant in proportion, slowly add them into 23.9 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0101] S2. Add 3 parts of nano zinc oxide as a nucleating agent to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0102] S3. Add 0.1 parts of diatomaceous earth as a crystal form modifier to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 h to obtain a third mixed solution.
[0103] S4. Add 2 parts of the performance optimizer gold sol to the third mixed solution, stir and mix, and stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a fourth mixed solution.
[0104] S5. Add 1 part of sodium carboxymethyl cellulose as a thickener to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0105] Comparative Example 2
[0106] A low-temperature phase change material with a phase change temperature of 2 to 8°C comprises the following components in parts by mass: 45 parts of a phase change refrigerant (including 35 parts of sodium hydroxide and 10 parts of sodium carbonate), 1 part of a nucleating agent of nano zinc oxide and 0.5 parts of carbon nanotubes (with a controlled particle size of about 120 μm), 1 part of a thickener of xanthan gum (with a controlled particle size of about 70 μm), 0.1 part of a crystal modifier of diatomaceous earth, and 53.4 parts of water.
[0107] The preparation method comprises the following steps:
[0108] S1. Take 35 parts of sodium hydroxide and 10 parts of sodium carbonate as phase change refrigerant in proportion, slowly add them into 53.4 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0109] S2. Add 1 part of nucleating agent nano zinc oxide and 0.5 parts of carbon nanotubes to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0110] S3. Add 0.1 parts of diatomaceous earth as a crystal form modifier to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 h to obtain a third mixed solution.
[0111] S4. Add 1 part of thickener xanthan gum to the third mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0112] Comparative Example 3
[0113] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 45 parts of a phase change refrigerant (including 35 parts of sodium hydroxide and 10 parts of sodium carbonate), 4 parts of a thickener xanthan gum (with a controlled particle size of about 50 μm), 0.1 parts of a crystal modifier diatomaceous earth (with a controlled particle size of about 50 μm), 5 parts of a performance optimizer gold sol (with the outer surface coated with a positive ion layer, the positive ion is H + , controlling the particle size to be about 50nm), 45.9 parts of water.
[0114] The preparation method comprises the following steps:
[0115] S1. Take 35 parts of sodium hydroxide and 10 parts of sodium carbonate as phase change refrigerant in proportion, slowly add them into 45.9 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0116] S2. Add 0.1 parts of diatomaceous earth as a crystal form modifier to the first mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 h to obtain a second mixed solution.
[0117] S3. Add 5 parts of performance optimizer gold sol to the second mixed solution, stir and mix, and stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a third mixed solution.
[0118] S4. Add 4 parts of thickener xanthan gum to the third mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0119] Comparative Example 4
[0120] A low-temperature phase change material with a phase change temperature of 2 to 8°C comprises the following components in parts by mass: 45 parts of a phase change refrigerant (including 35 parts of sodium hydroxide and 10 parts of sodium carbonate), 1 part of a nucleating agent of nano zinc oxide and 0.5 parts of carbon nanotubes (controlling a particle size of about 150 μm), 0.1 part of a crystal modifier of diatomaceous earth (controlling a particle size of about 80 μm), 5 parts of a performance optimizer of gold sol (controlling a particle size of about 1 nm), and 48.4 parts of water.
[0121] The preparation method comprises the following steps:
[0122] S1. Take 35 parts of sodium hydroxide and 10 parts of sodium carbonate as phase change refrigerant in proportion, slowly add them into 48.4 parts to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0123] S2. Add 1 part of nucleating agent nano zinc oxide and 0.5 parts of carbon nanotubes to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0124] S3. Add 0.1 parts of diatomaceous earth as a crystal form modifier to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 h to obtain a third mixed solution.
[0125] S4. Add 5 parts of performance optimizer gold sol to the third mixed solution, stir and mix, and stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a phase change material.
[0126] Comparative Example 5
[0127] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 45 parts of a phase change refrigerant (including 35 parts of sodium hydroxide and 10 parts of sodium carbonate), 1 part of a nucleating agent, nano zinc oxide, and 0.5 parts of a carbon nanotube (with a controlled particle size of about 150 μm), 4 parts of a thickener, xanthan gum (with a controlled particle size of about 50 μm), and 5 parts of a performance optimizer, gold sol (with a positive ion layer on the outer surface, wherein the positive ion is H + , controlling the particle size to be about 40nm), 44.5 parts of water.
[0128] The preparation method comprises the following steps:
[0129] S1. Take 35 parts of sodium hydroxide and 10 parts of sodium carbonate as phase change refrigerant in proportion, slowly add them into 44.5 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0130] S2. Add 1 part of nucleating agent nano zinc oxide and 0.5 parts of carbon nanotubes to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0131] S3. Add 5 parts of performance optimizer gold sol to the second mixed solution, stir and mix, and stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a third mixed solution.
[0132] S4. Add 4 parts of thickener xanthan gum to the third mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0133] Comparative Example 6
[0134] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 45 parts of a phase change refrigerant (45 parts of sodium hydroxide), 1 part of a nucleating agent, nano zinc oxide, and 0.5 parts of carbon nanotubes (controlling a particle size of about 150 μm), 4 parts of a thickener, xanthan gum (controlling a particle size of about 50 μm), 0.1 parts of a crystal modifier, diatomaceous earth (controlling a particle size of about 50 μm), and 5 parts of a performance optimizer, gold sol (all of which are coated with a positive ion layer on the outer surface, and the positive ions are H + , controlling the particle size to be about 60nm), 44.4 parts of water.
[0135] The preparation method comprises the following steps:
[0136] S1. Take 45 parts of sodium hydroxide, a phase-change refrigerant, in proportion, slowly add it into 44.4 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0137] S2. Add 1 part of nucleating agent nano zinc oxide and 0.5 parts of carbon nanotubes to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0138] S3. Add 0.1 parts of diatomaceous earth as a crystal form modifier to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 h to obtain a third mixed solution.
[0139] S4. Add 5 parts of performance optimizer gold sol to the third mixed solution, stir and mix, stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a fourth mixed solution.
[0140] S5. Add 4 parts of thickener xanthan gum to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0141] Comparative Example 7
[0142] A low-temperature phase change material with a phase change temperature of 2 to 8°C, comprising the following components by mass: 20 parts of a phase change refrigerant (20 parts of sodium carbonate), 1 part of a nucleating agent, nano zinc oxide, and 0.5 parts of carbon nanotubes (with a controlled particle size of about 150 μm), 4 parts of a thickener, xanthan gum (with a controlled particle size of about 50 μm), 0.1 parts of a crystal modifier, diatomaceous earth (with a controlled particle size of about 50 μm), and 5 parts of a performance optimizer, gold sol (with the outer surface of each part coated with a positive ion layer, the positive ions being H + , controlling the particle size to be about 70nm), and 69.4 parts of water.
[0143] The preparation method comprises the following steps:
[0144] S1. Take 20 parts of phase change coolant sodium carbonate in proportion, slowly add it into 69.4 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0145] S2. Add 1 part of nucleating agent nano zinc oxide and 0.5 parts of carbon nanotubes to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0146] S3. Add 0.1 parts of diatomaceous earth as a crystal form modifier to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 h to obtain a third mixed solution.
[0147] S4. Add 5 parts of performance optimizer gold sol to the third mixed solution, stir and mix, stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a fourth mixed solution.
[0148] S5. Add 4 parts of thickener xanthan gum to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0149] Comparative Example 8
[0150] A low-temperature phase change material with a phase change temperature of 2-8°C comprises the following components in parts by mass: 98 parts of n-tetradecane as a phase change cooling agent, 1 part of talcum powder as a nucleating agent, and 1 part of sodium polyacrylate as a thickener.
[0151] The preparation method comprises the following steps:
[0152] S1. Add 98 parts of n-tetradecane as a phase-change refrigerant under stirring at a temperature of 25° C., a stirring rate of 400 rpm, and a stirring time of 1 h to obtain a first mixed solution.
[0153] S2. Add 1 part of nucleating agent talcum powder to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0154] S3. Add 1 part of thickener sodium polyacrylate to the second mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0155] Comparative Example 9
[0156] A low-temperature phase change material with a phase change temperature of 2 to 8°C comprises the following components in parts by mass: 45 parts of a phase change refrigerant (35 parts of sodium hydroxide and 10 parts of sodium carbonate), 1.5 parts of a nucleating agent (1 part of nano zinc oxide and 0.5 parts of carbon nanotubes, with a controlled particle size of about 10 μm), 4 parts of a thickener xanthan gum (with a controlled particle size of about 20 μm), 0.1 parts of a crystal modifier diatomaceous earth (with a controlled particle size of about 20 μm), 5 parts of a performance optimizer gold sol (with the outer surface not coated with a positive ion layer, with a controlled particle size of about 1 nm), and 44.4 parts of water.
[0157] The preparation method comprises the following steps:
[0158] S1. Take 35 parts of sodium hydroxide and 10 parts of sodium carbonate as phase change refrigerant in proportion, slowly add them into 44.4 parts of water to dissolve, stir and mix evenly, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a first mixed solution.
[0159] S2. Add 1 part of nucleating agent nano zinc oxide and 0.5 parts of carbon nanotubes to the first mixed solution, stir and mix, and stop stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a second mixed solution.
[0160] S3. Add 0.1 parts of diatomaceous earth as a crystal form modifier to the second mixed solution, stir and mix, and stop stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state. The stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 h to obtain a third mixed solution.
[0161] S4. Add 5 parts of performance optimizer gold sol to the third mixed solution, stir and mix, stop stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 400 rpm, and the stirring time is 1 hour to obtain a fourth mixed solution.
[0162] S5. Add 4 parts of thickener xanthan gum to the fourth mixed solution, stir and mix evenly, stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state, the stirring temperature is 25° C., the stirring rate is 600 rpm, and the stirring time is 2 h to obtain a phase change material.
[0163] Performance tests were performed on Examples 1-6 and Comparative Examples 1-9, and the test results are shown in the following table:
[0164] Table 1. Performance test results of phase change materials of Examples 1-6 and Comparative Examples 1-9
[0165]
[0166]
[0167] It can be seen from the above table that in an embodiment of the present invention, an inorganic salt composite phase change refrigerant and water are used as a phase change matrix, and a crystal modifier, a nucleating agent and a thickener are used to prepare a phase change material for storing and releasing cold. The prepared phase change material can have a phase change temperature of 2 to 8°C, a phase change latent heat of >260 kJ / kg, a thermal conductivity of >1.1 W / (m·K), a density of >1.6 g / cm3, a volume expansion rate of <0.5%, a supercooling degree of <1°C, and good cyclic stability.
[0168] Compared with Examples 1-6, the phase change temperature, phase change latent heat, thermal conductivity density, volume expansion rate, and supercooling of the phase change materials of Comparative Examples 1-9 are all inferior to those of the phase change materials of the present invention; the phase change temperature of the phase change material of Comparative Example 1 does not reach 2-8°C, and the phase change latent heat is low; Comparative Example 2 does not add a performance optimizer, resulting in a phase change latent heat of less than 260 kJ / kg, a volume expansion rate greater than 0.5%, a supercooling greater than 1°C, and general cycle stability; Comparative Example 3 does not add a nucleating agent, resulting in a supercooling greater than 10°C before and after the cycle, which is too large, affecting the practical application of the material, causing overtemperature, and the time to cool to the target temperature range of 2-8°C is prolonged, and the thermal conductivity is reduced (because there is no nucleating agent with high thermal conductivity); Comparative Example 4 does not add a thickener, resulting in phase stratification, especially after long-term standing or circulation, the phase stratification is serious, which further affects the supercooling of the phase change material, increases the temperature unevenness during insulation, and the phase change temperature of some materials is not in the insulation range; Comparative Example 5 does not add a crystal The phase change temperature and the latent heat of phase change are reduced, and the performance after the cycle is further reduced; Comparative Examples 6 and 7 use a single phase change refrigerant, and the phase change temperature is too low (1.8°C) or too high (26.4°C), the latent heat of phase change is reduced, and the cycle stability is reduced; Comparative Example 8 uses an organic phase change refrigerant, and the prepared phase change material has low density, low latent heat of phase change, small thermal conductivity, and large solid-liquid volume expansion rate. The large volume expansion rate leads to less phase change material that can be filled in the ice block (or other fixed container) under the same volume, which reduces the insulation time; the higher the volume expansion rate, the easier it is to cause the ice block (or other container) to bulge, expand, or even rupture, and it is easy to leak; the outermost layer of the performance optimizer in Comparative Example 9 is not coated with positive ions, and the performance optimizer not coated with positive ions cannot form a larger three-dimensional layered structure with the network structure formed by the phase change refrigerant and the crystal form modifier, which affects the stability, latent heat of phase change and supercooling of the phase change material.
[0169] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A phase change material having a phase change temperature of 2 to 8°C, characterized in that: The invention comprises the following components in parts by weight: 30 to 50 parts of a phase-change refrigerant, 0.3 to 3 parts of a nucleating agent, 0.5 to 8 parts of a thickener, 0.1 to 1 parts of a crystal modifier, 1 to 5 parts of a performance optimizer, and 35 to 70 parts of water; The phase-change coolant comprises at least two of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, barium hydroxide, calcium hydroxide, ammonia water, potassium bicarbonate, sodium bicarbonate, potassium chloride, sodium chloride, barium chloride, potassium nitrate, sodium acetate, sodium sulfate, and disodium hydrogen phosphate; The crystal modifier is at least one of diatomaceous earth, activated clay, soluble starch, fumed silica, viscose fiber, acetate fiber, polyester, acrylic fiber, spandex, chloroprene, glass fiber, and asbestos; The performance optimizer is a spherical structure, and the outer surface of the performance optimizer is coated with a positive ion layer; The nucleating agent is at least one of nano-carbon powder, graphite powder, nano-zinc oxide, nano-aluminum oxide, nano-copper, nano-silicon nitride, carbon nanotubes, and carboxylated multi-walled carbon nanotubes; The thickener is at least one of polyacrylamide, sodium polyacrylate, sodium carboxymethyl cellulose, sodium hydroxymethyl cellulose, xanthan gum, guar gum, activated clay, gelatin, attapulgite, gum arabic, pectin, agar, tamarind gum, β-cyclodextrin, sodium carboxymethyl starch, and hydroxypropyl starch; The performance optimizer is at least one of gold sol, silver sol, copper sol and aluminum sol; The particle size of the crystal modifier is 20 to 100 μm; the particle size of the nucleating agent is 10 to 200 μm; the particle size of the thickener is 20 to 100 μm; and the particle size of the performance optimizer is 1 to 100 nm.
2. The phase change material with a phase change temperature of 2 to 8° C. according to claim 1, characterized in that: The positive ion layer is an H+ layer.
3. A method for preparing a phase change material having a phase change temperature of 2 to 8° C. according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, taking a phase change refrigerant in proportion, slowly adding it into water to dissolve, stirring and mixing evenly to obtain a first mixed solution; S2, adding a nucleating agent to the first mixed solution, stirring and mixing, and stopping stirring when the nucleating agent is completely dissolved and the solution is in a uniform fluid state, to obtain a second mixed solution; S3, adding a crystal form modifier to the second mixed solution, stirring and mixing, and stopping stirring when the crystal form modifier is completely dissolved and the solution is in a uniform fluid state, to obtain a third mixed solution; S4, adding the performance optimizer to the third mixed solution, stirring and mixing, and stopping stirring when the performance optimizer is completely dissolved and the solution is in a uniform fluid state, to obtain a fourth mixed solution; S5. Add a thickener to the fourth mixed solution, stir and mix evenly, and stop stirring when the thickener is completely dissolved and the solution is in a uniform fluid state to obtain a phase change material.
4. The method for preparing a phase change material having a phase change temperature of 2 to 8°C according to claim 3, characterized in that: In step S1, the stirring temperature is 25-35° C., the stirring rate is 400-600 rpm, and the stirring time is 1-2 h.
5. The method for preparing a phase change material having a phase change temperature of 2 to 8°C according to claim 3, characterized in that: In step S2, the stirring temperature is 25-35°C, the stirring speed is 400-600 rpm, and the stirring time is 1-2 h.
6. The method for preparing a phase change material with a phase change temperature of 2 to 8°C according to claim 3, characterized in that: In step S3, the stirring temperature is 20-35° C., the stirring rate is 400-600 rpm, and the stirring time is 1-2 h.
7. The method for preparing a phase change material with a phase change temperature of 2 to 8°C according to claim 3, characterized in that: In step S4, the stirring temperature is 25-35° C., the stirring speed is 400-600 rpm, and the stirring time is 1-2 h.
8. The method for preparing a phase change material with a phase change temperature of 2 to 8°C according to claim 3, characterized in that: In step S5, the stirring temperature is 20-35° C., the stirring rate is 600-800 rpm, and the stirring time is 2-4 h.
Citation Information
Patent Citations
Preparation method for coolant for refrigerating transportation box
CN107573900A
Composite phase-change material used at temperature of 2-8 DEG C and preparation method thereof
CN108251068A